Factors Affecting the Incidences of Needle Stick Injury on The Nurses Emergency Department of Hospital East Java (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hospital with all the facilities and equipment that can be a source of health and safety hazards of potential,especially for health workers if no management following the standards of safety and health procedurekerjaNeedle stick and sharp object injuries is a significant challenge for health workers, and nurses arejobs are most often associated with the incidence of needle stick injury. The purpose of this study wasto determine the factors that influence the prevalence of needle stick injury to nurses in the emergencydepartment of hospital Eas Java. This study using 64 samples from a total of as many as 76. The ER nursethat most of the variables age category ? 29 years, ? five years of working life, has never participated inoccupational safety and health training, and education level diploma 3 — workers who perform unsafeactions as much as 37.5%. The Bivariable analysis showed that age, work periode, education level, andtraining has a significant value above 0.05 was no meaningful relationship to the needle stick injury. Unsafeaction was a value of 0.026, which means significance was a substantial relationship with a needle stickinjury. The multivariable nurses who perform dangerous activities are at increased risk of needle stick injury4x compared to nurses who work safely. Prevention of occupational accidents to human factors include laborregulations taking into account the limits of the abilities and skills of workers, nullify the things that reducethe concentration of workers, enforce work discipline, avoid actions that bring accidents and eliminate theirphysical and mental incompatibility.